Uncovering the potential of Yiqi Huoxue Jiedu formula: a promising adjunct in sepsis and septic shock management - Huang, Peiying; Chen, Bingrui; Yang, Xiaorong; Chen, Houguang; Tang, Jiaqi; Chen, Rui; Li, Jun; Ye, Ye (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundSepsis and septic shock represent severe infectious conditions with challenging treatments. Preliminary animal studies indicate that Yiqi Huoxue Jiedu Formula (YHJF) may enhance sepsis outcomes, but no clinical trials have been conducted. This research aims to substantiate the efficacy of YHJF in treating sepsis and septic shock.Materials and methodsMass spectrometry was used to identify the absorbed constituents of YHJF. A retrospective cohort study included sepsis patients from four sub-centers (Feb 24, 2016 - Oct 31, 2024), divided into Western treatment and YHJF plus Western care groups. Propensity score matching ensured baseline comparability. The primary outcome was 28-day mortality, with secondary outcomes including intensive care units (ICU) and hospital stay duration, mechanical ventilation and renal replacement therapy duration, fever duration, and changes in SOFA and APACHE II scores, blood procalcitonin, white blood cell count, and lactate levels after 5 days of treatment. Sepsis shock was analyzed as a subgroup.ResultsYHJF absorption mainly includes Shikimates and Phenylpropanoids (33%), Terpenoids (21%), Alkaloids (14%), and Polyketides (11%). A total of 389 sepsis patients were enrolled, with 82 patients being identified as septic shock in the clinical study. The clinical results indicated that YHJF may shorten hospital stay duration, reduce ventilator duration, and improve SOFA score in sepsis. For septic shock, YHJF administration could reduce the duration of non-invasive ventilator use. Notably, YHJF has no effect on improving 28-day mortality for sepsis and septic shock.ConclusionYHJF can reduce the SOFA score, ventilator use duration, and hospital stay length in sepsis cases and improve non-invasive ventilator use time in septic shock patients, which might attribute to the absorbed components after YHJF administration. Further high-quality trials are needed for confirmation.